«Գահնամակ ազատաց եւ տանուտէրանց հայոց». Հետազօտութիւն եւ բնագիր - Յակոբեան, Ալեքսան («Զանգակ - 97»)
In the article a new historic-philological analyse of Armenian unique, early medieval document, namely “Gahnamak” (Throne List, Ranking List), and its scientific-critical text is presented.
Keywords: Գրականութիւն; Պատմութիւն